Numerical Analysis of load – Settlement Response of Piled Raft Foundation in Layered Soil Using Plaxis 3D Numerical Model - Sicko Jara (ASTU, 2026)
Urban growth has led to large buildings on soft soil due to limited firm building site and rocky ground formations, causing excessive and differential settlement issues in cities with less stable base. Strict safety rules require minimal uneven settlement in high-rise buildings. Piled raft foundations have become a popular solution, using piles to reduce settlement and share the building's weight. In this study the analysis of load-settlement behavior of piled raft foundation using numerical methods was carried out. The performance of a rectangular piled raft system is evaluated in layered soil subjected to uniform vertical loading. The analysis is conducted using the powerful finite element-based program Plaxis 3D to examine the effects of various parameters. A parametric study is also conducted to investigate the response of piled-raft foundations, including the influence of raft thickness, pile length, and pile spacing, while keeping the pile diameter and the number of piles constant. The results from the analysis indicated that by applying a piled raft to an un-piled raft foundation with a raft thickness of 2 m, the maximum settlement was reduced from 102.7 mm to 77.57mm, and the differential settlement also decreased from 11.9 mm to 2.09 mm. This represents a decrease of 24.47% and 82.44%, respectively, for a case with 2D pile spacing and an 18 m pile length. By increasing the pile spacing from 2D to 3D, the maximum settlement was reduced by 17.18% for an 18 m pile length and a 3 m raft thickness. Furthermore, a total settlement reduction of 24.18% was achieved by increasing the pile length from 10.8 m to 18 m, under the conditions of 3D pile spacing and a 3 m raft thickness. Hence, the findings from this research can serve as a framework for developing large combined piled-raft foundations to support heavy building structures and provide a methodological approach for future projects involving complex soil-structure interactions.